2015
DOI: 10.4161/19336918.2014.983799
|View full text |Cite
|
Sign up to set email alerts
|

MMP1 gene expression enhances myoblast migration and engraftment following implanting into mdx/SCID mice

Abstract: Myoblast transplantation (MT) is a method to introduce healthy genes into abnormal skeletal muscle. It has been considered as a therapeutic modality in the last few decades for diseases such as Duchenne Muscular Dystrophy (DMD). However, challenges including cell death and poor graft engraftment have limited its application. The current experiment utilizes MMP1 gene transfer to improve the efficacy of myoblast transplantation into the diseased dystrophic skeletal muscle of mdx mice. Our results indicated that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 49 publications
(52 reference statements)
0
14
0
Order By: Relevance
“…This pretreatment made the subsequent systemic injection of myogenic capable mesoangioblasts able to engraft, leading to α-sarcoglycan positive muscle fibers. In a more concise manner, myoblasts themselves were transfected with an MMP-1 expression vector which permitted more robust engraftment and expression of dystrophin in an immunocompromised mdx mouse [117]. Together these studies emphasize the reality that fibrosis presents a barrier to donor cell delivery and engraftment into diseased muscle that in certain instances can be overcome by providing anti-fibrotic treatment in conjunction with cell therapy.…”
Section: Fibrosis and Cell Therapy In Muscular Dystrophymentioning
confidence: 99%
“…This pretreatment made the subsequent systemic injection of myogenic capable mesoangioblasts able to engraft, leading to α-sarcoglycan positive muscle fibers. In a more concise manner, myoblasts themselves were transfected with an MMP-1 expression vector which permitted more robust engraftment and expression of dystrophin in an immunocompromised mdx mouse [117]. Together these studies emphasize the reality that fibrosis presents a barrier to donor cell delivery and engraftment into diseased muscle that in certain instances can be overcome by providing anti-fibrotic treatment in conjunction with cell therapy.…”
Section: Fibrosis and Cell Therapy In Muscular Dystrophymentioning
confidence: 99%
“…Several substances that modulate p38-MAPK, NF-kB, NO-cGMP [116, 118, 200–203], inhibit TGF-β [204], reduce oxidative stress [205] or inflammation [206, 207] have had beneficial effects in muscular dystrophies and deserve to be tested, in preclinical settings, in combination with short-term, transitory MMP-9 inhibition. With the exception of MMP-9 that plays a dual role in skeletal muscle regeneration/dystrophy [110, 208, 209], the inhibition of other MMPs proved they are essential for efficient muscle regeneration -this review and [210]-, reduction of fibrosis [211] and amelioration of myoblast engraftment following implantation into dystrophic mice [212]. This confirms the necessity for questioning long-term inhibition of MMPs not only in cancer and inflammation [213] but also in muscular dystrophies and other muscle diseases.…”
Section: Discussionmentioning
confidence: 99%
“…MMPs belong to the proteolytic enzyme family that participates in degradation of the basement membrane and extracellular matrix (ECM) (Ries et al, 2007). The matrix metalloproteinase-1 (MMP1), acting through the MMP1/PAR1 axis, causes decay of the interstitial collagen type I, II and III (Ho et al, 2009;Pan et al, 2014). It has been proven that upregulation of MMP1 expression leads to a high migration capacity of MSCs.…”
Section: Factors Involved In Mscs Migrationmentioning
confidence: 99%
“…It has been proven that upregulation of MMP1 expression leads to a high migration capacity of MSCs. In vitro studies have shown that knockdown of the MMP1 gene in MSCs results in inhibition of their migration capacity (Pan et al, 2014). Thus, cells with high MMP1 expression can be a valuable agent in clinical therapy affecting the possibility of cell engraftment at the target site.…”
Section: Factors Involved In Mscs Migrationmentioning
confidence: 99%